Identifikasi Potensi Budidaya Jamur Dalam Perencanaan Calon Desa Wisata Banjardowo Semarang - Mochamad Ainan; Pranoto Pranoto; Ahmad Syuraih Musyary; Yusuf Tri Wahyudin; Novia Ekin Ramadhani; Abdul Charis (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2022)
The tourism sector is an effort that can increase local revenue and development. However, the tourism sector still has several obstacles so that appropriate strategies are needed to develop tourism by several elements of society. One approach to realizing tourism development is to package a village into a tourist village. Banjardowo is a village in the Genuk sub-district, Semarang City, Central Java Province, Banjardowo Village plans to become a tourism village that has the potential for oyster mushrooms. The JAB community even took the initiative to develop and cultivate oyster mushrooms, and make the surrounding location one of the new natural tourist destinations based on processed mushrooms. The research method used in this study uses qualitative research methods where in collecting data using purposive sampling technique (research determines criteria regarding which respondents will be selected as samples).